Tropomyosin-2 cDNA lacking the 3' untranslated region riboregulator induces growth inhibition of v-Ki-ras-transformed fibroblasts. - Janssen, R A (1997)
The levels of high molecular weight isoforms of tropomyosin (TM) are markedly reduced in ras-transformed cells. Previous studies have demonstrated that the forced expression of tropomyosin-1 (TM-1) induces reversion of the transformed phenotype of ras-transformed fibroblasts. The effects of the related isoform TM-2 on transformation are less clear. To assess the effects of forced expression of the TM-2 protein on ras-induced tumorigenicity, we introduced a TM-2 cDNA lacking the 3' untranslated region riboregulator into ras-transformed NIH 3T3 fibroblasts. TM-2 expression resulted in a flatter cell morphology and restoration of stress fibers. TM-2 expression also significantly reduced growth rates in low serum, soft agar, and nude mice. The reduced growth rates were associated with a prolongation of G0-G1. To identify the mechanism of TM-2-induced growth inhibition, we analyzed the effects of TM-2 reexpression of ERK and c-jun N-terminal kinase (JNK) activities. Levels of ERK phosphorylation and activity in TM-2-transfected tumor cells were comparable to those in mock-transfected tumor cells. JNK activity was only modestly increased in ras-transformed cells relative to untransformed NIH 3T3 cells and only slightly reduced as result of forced TM-2 expression. We conclude that the partially restored expression of the TM-2 protein induces growth inhibition of ras-transformed NIH 3T3 cells without influencing ERK or JNK activities. Furthermore, the 3' untranslated region riboregulator of the alpha-tropomyosin gene is not needed for the inhibition of ras-induced growth.